3.3 Excavations at Sand, the flaked lithic assemblage (Scottish Historical and Archaeological Internet Reports, 2009)
Over 16,500 pieces of flaked stone have been recovered, 451 pieces prior to excavation and over 16,000 pieces from the main excavation in 2000.